Optic Neuritis in Farwestern and Midwestern Region of Nepal: A Hospital Based Study - Thapa, Bikram Bahadur; Dhakal, Yogesh (Journal of Nepalgunj Medical College, 2017)
Background: optic neuritis is a common cause of visual loss. Its demographic and clinical picture is different in the eastern and western countries. The treatment outcomes are also different in report from different place. Its data is lacking in the Midwestern and Far western Nepal. Objective: To report its clinical features, demographic pattern and response to treatment in the patients of this region. Materials and methods: The hospital based data of patients of Nepalgunj medical college were analyzed retrospectively with respect from September 2016 to June 2017. Results: Sixteen patients (20 eyes) were found to have optic neuritis (papillits in 13 and retrobulbar optic neuritis in 7 eyes). The male to female ratio was 1:1.29. The mean age of the patients was 27.63 ±12.48 years (95% CI=21.88 – 34.00). The most common modes of presentation was decrease in vision and color vision defect. One patient had multiple sclerosis at the presentation revealed by MRI with plaque in occipital cortex. Visual outcome was encouraging in all cases with pulse steroid therapy (p=0.002). Conclusion: Pulse methylprednisolone therapy is found to have better prognostic results. In demographic pattern younger population is found more affected in our study than other reports.